2018
DOI: 10.1021/acsnano.8b07225
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Bond Topologies in Open-Shell Graphene Nanostructures

Abstract: Polycyclic aromatic hydrocarbons exhibit a rich spectrum of physico-chemical properties depending on the size, and more critically, on the edge and bond topologies. Among them, open-shell systems-molecules hosting unpaired electron densities-represent an important class of materials for organic electronic, spintronic and optoelectronic devices, but remain challenging to synthesize in solution. We report the on-surface synthesis and scanning tunneling microscopy-and spectroscopy-based study of two ultra-low-gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
111
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(119 citation statements)
references
References 65 publications
4
111
1
3
Order By: Relevance
“…This strategy could eventually be employed in the preparation of graphene nanoribbons containing five‐membered rings, because such a modification at specific positions can allow for the fine‐tuning of electronic properties. According to the same strategy, ultra‐low‐gap open‐shell molecules, such as peri ‐tetracene ( 240 from 239 ), a benzenoid graphene fragment with a zigzag edge topology, and dibenzo[ a , m ]dicyclohepta[ bcde , nopq ]rubicene ( 242 from 241 ), a nonbenzenoid nonalternant structural isomer of peri ‐tetracene with two embedded azulene units, were synthesized by surface‐assisted CDH (Scheme C). Spin‐polarized DFT calculations revealed that both compounds should exhibit an open‐shell singlet ground state, thus making them promising candidates for spintronic applications.…”
Section: Surface‐assisted (Cyclo)dehydrogenation (Cdh)mentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy could eventually be employed in the preparation of graphene nanoribbons containing five‐membered rings, because such a modification at specific positions can allow for the fine‐tuning of electronic properties. According to the same strategy, ultra‐low‐gap open‐shell molecules, such as peri ‐tetracene ( 240 from 239 ), a benzenoid graphene fragment with a zigzag edge topology, and dibenzo[ a , m ]dicyclohepta[ bcde , nopq ]rubicene ( 242 from 241 ), a nonbenzenoid nonalternant structural isomer of peri ‐tetracene with two embedded azulene units, were synthesized by surface‐assisted CDH (Scheme C). Spin‐polarized DFT calculations revealed that both compounds should exhibit an open‐shell singlet ground state, thus making them promising candidates for spintronic applications.…”
Section: Surface‐assisted (Cyclo)dehydrogenation (Cdh)mentioning
confidence: 99%
“…[270] Specifically,t he molecular precursor 232 undergoes polymerization followed by as eries of CDH processes to afford graphene nanoribbon 234 with azigzag edge topology (Scheme 31 A). This concept was further extended to dibromodimethylterphenyl 235 (Scheme 31 B), [271] where the polymerization/surface-assistedo xidative ring-closure sequence between am ethyl group and the neighboring aryl moiety gives rise to indenofluorene-based polymers 237 and 238.This strategy could eventually be employed in the preparation of graphene nanoribbons containing five-membered rings, because such am odification at specific positions can allow for the fine-tuning of electronic properties.A ccording to the same strategy,u ltra-low-gap open-shell molecules,s uch as peri-tetracene (240 from 239), ab enzenoid graphene fragment with az igzag edge topology,a nd dibenzo-[a,m]dicyclohepta[bcde,nopq]rubicene (242 from 241), anonbenzenoid nonalternant structural isomer of peri-tetracene with two embedded azulene units,w ere synthesized [272] by surface-assisted CDH (Scheme 31 C). Spin-polarized DFT calculations revealed that both compounds should exhibit an open-shell singlet ground state,t hus making them promising candidates for spintronic applications.…”
Section: Surface-assisted (Cyclo)dehydrogenation (Cdh)mentioning
confidence: 99%
“…Non‐benzenoid rings can be spontaneously formed during nanomaterials preparation. The formation of four‐membered rings by adjusting the active site at the adjacent position, the formation of five‐membered rings through the cyclization of a methyl group against a neighboring aromatic unit or the removal of atoms of active heterocyclic group and even dehydrocyclization of intra‐molecule, and other‐rings originate from the inter‐ribbon cross‐dehydrogenative coupling can be included as examples. GNRs with periodically embedded four‐ and eight‐membered rings called graphene‐like nanoribbon and, can be synthesized by bottom‐up approach on Au(111) (shown Figure a and Figure b) .…”
Section: Tuning the Electronic Propertiesmentioning
confidence: 99%
“…On-surface synthesis has been widely used to fabricate atomically precise covalent nanoarchitectures by using small molecular monomers as building blocks. [1][2][3][4][5] In the past decade, many functional nanomaterials have been successfully synthesized and characterized on various surfaces by using ultra-vacuum and surface science techniques, [6] such as single molecules, [7][8][9][10] one-dimensional nanowires, [11][12][13] one-dimensional nanoribbons, [14][15][16] and small patches of two-dimensional covalent networks. [17,18] In these works, various reactions have been successfully realized on surfaces, like Ullmann coupling reaction, [19,20] dehydrogenation reactions, [21,22] cyclization chemistry, [23][24][25] to name a few.…”
Section: Introductionmentioning
confidence: 99%